Nano-tribological characterisation of palm oil-based trimethylolpropane ester for application as boundary lubricant. (November 2018) - Hamdan, S.H.; Chong, W.W.F.; Ng, J.-H.; Chong, C.T.; Zhang, H.
Abstract: To isolate shearing of boundary film from direct surface-to-surface asperity interactions, the study determines boundary lubrication properties of palm oil-based TMPE (PTMPE) using Lateral Force Microscopy coupled with fluid imaging. PTMPE is produced through a series of 3-step transesterification processes, converting palm oil (PO) into palm methyl ester (PME) and finally into PTMPE. It is shown that PME generates the lowest friction. However, using Eyring thermal activation energy approach, PME is shown to possess less desirable load bearing property, portraying a form of stiction or adhesive nature. Even though friction is higher, PTMPE exhibits better load bearing ability, demonstrating the onset of lubricant laminar flow due to increased hydrodynamic effect, which is not observed for the PO and PME measurements. Highlights: The study explores the use of palm based TMPE (PTMPE) as boundary lubricant additive. PTMPE is produced using a series of 3-step transesterification processes from palm oil. PTMPE boundary lubrication properties are measured using Lateral Force Microscopy. Frictional properties are interpreted as a function of thermal activation energies. PTMPE exhibits good load bearing ability due to more effectively formed boundary film.